Optimization of Employee Productivity in the Production Section at PT. X: The Role of Educational Level and Physical Work Environment - Hilda Fitria; Fetty Poerwita Sary (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to determine the effect of education level and physical work environment on the work productivity of production employees at PT. X. Design/Methodology/Approach – In this study, the authors used a quantitative method. The number of employees in this study were 111 production employees at PT. X. Analysis testing using SPSS Version 26. Findings – The results showed that there was a positive and significant influence between the level of education and the physical work environment on employee work productivity. Conclusions and Implications - The level of education and physical work environment have a positive effect on employee work productivity, thereby increasing the work productivity of employees PT. X needs to consider higher levels of employee education as well as improving the company's physical work environment.